Dampak Green Accounting dan Corporate Social Responsibility (CSR) dengan Kinerja Keuangan Melalui Nilai Perusahaan pada Perusahaan Sektor Pertambangan di Bursa Efek Indonesia: Studi Periode 2020-2024 - Devina Shava Amalia; Slamet Riyadi (OPTIMAL Jurnal Ekonomi dan Manajemen, 2026)
This study is useful for examining how the implementation of Green Accounting and Corporate Social Responsibility (CSR) affects Financial Performance through Company Value in mining businesses listed on the IDX between 2020 and 2024. The Indonesia Stock Exchange (IDX) website was used to collect data for this study between September and November 2025. The data sources are secondary, and the data applied is quantitative. The study findings show that green accounting significantly affects company value and financial performance, although the effect can be negative in the short term due to increased operating costs. Meanwhile, Financial performance and company value are not significantly impacted by corporate social responsibility (CSR), as its positive impact is more long-term and does not directly affect ROA and ROE. In addition, company value does not act as a mediator linking Green Accounting or CSR to financial performance, confirming that other factors such as cost efficiency and market conditions have a greater influence on a company’s financial results.